HTK-N, a modified HTK solution, decreases preservation injury in a model of microsteatotic rat liver transplantation - Liu, Qinlong; Bruns, Helge; Schultze, Daniel; Xue, Yi; Zorn, Markus; Flechtenmacher, Christa; Straub, Beate Katharina; Schemmer, Peter (Langenbeck's archives of surgery, 2012)
Background Ischemia/reperfusion injury is an obstacle especially in steatotic livers, including those with steatosis induced by acute toxic stress. Recently, a modified...
Gesehen am 21.11.2018